Can we improve teaching and learning of percutaneous dilatational tracheostomy's bronchoscopic guidance?. (March 2021) - Abbott, Francisco; Ortega, Marcos; Bravo, Sebastian; Basoalto, Roque; Kattan, Eduardo
Percutaneous dilatational tracheostomy has become the technique of choice in multiple intensive care units. Among innovations to improve procedural safety and success, bronchoscopic guidance of percutaneous dilatational tracheostomy has been advocated and successfully implemented by multiple groups. Most published literature focuses on the percutaneous dilatational tracheostomy operator, with scarce descriptions of the bronchoscopic particularities of the procedure. In this article, we provide 10 suggestions to enhance specific procedural aspects of bronchoscopic guidance of percutaneous dilatational tracheostomy, and strategies to optimize its teaching and learning, in order to promote learners' competence acquisition and increase patient safety.